Knowledge, Attitude, Practice and Food Poisoning Associated Factors Among Parents in Bench-Sheko Zone, Southwest Ethiopia - Mekonnen, Besufekad (Int J Gen Med, 2021)
BACKGROUND: Food poisoning is a food borne disease, mainly resulting from ingestion of food that contains a toxin, chemical or infectious microorganisms like bacteria, virus, parasite, or prion. On the other hand, avoiding food contamination during preparing and feeding is a key factor for reducing the prevalence of food poisoning. This study aimed to assess the knowledge, attitude, self-reported practice and food poisoning associated factors among parents in the selected health centers of Bench-Sheko Zone in Ethiopia. METHODS: An institution-based cross-sectional study was conducted among 408 systematically selected parents in Bench-Sheko zone, Ethiopia. The data were collected through face to face interview using a structured questionnaire. RESULTS: The median knowledge score was 8.0 with an interquartile range (IQR) of 8.0–10.0. The median attitude score was 9.0 with an IQR of 6.0–9.0. The median practice score was 12.0 with an IQR of 10.0–13.0. A positive correlation was seen between knowledge and attitudes of parents with food poisoning (r= 0.321, P < 0.026), between knowledge and practices of parents towards food poisoning (r= 0.312, P < 0.001) and between attitude and practices result towards food poisoning (r= 0.224, p < 0.031). The parents with a higher education level, employed and who live in a city were the factors significantly associated with higher knowledge scores (p < 0.05). The improved attitude was seen as educational level increased (p <0.05). The parents with female gender, employed and who live in a city were significantly associated with higher hygienic practices towards the prevention of food poisoning (p <0.05). CONCLUSION: The knowledge, attitude, and self-reported practices of parents regarding food poisoning prevention are associated with each other and are affected by socio-demographic variables. Therefore, adequate emphasis should be given by health sectors to designing strong strategies which address the specific contributing factors for the problem.